Pola Pelaksanaan Manajemen Bimbingan dan Konseling di Sekolah Menengah Atas - M. Harwansyah Putra Sinaga; Khairina Qurrata; Vina Andini (Kuras Institute, 2022)
The purpose of this study was to reveal the implementation of the guidance and counseling management pattern at SMA Al-Ulum Medan. This research used a descriptive qualitative approach with the case study research. Data was collected by using observation, interview, and document. The data analysis technique used was the Miles and Huberman analysis model. The subjects were three school counselors at SMA Al-Ulum Medan. The results of this study explain that guidance and counseling management pattern implemented at SMA Al-Ulum Medan is POP BK. The implementation of counseling services are manifested in basic services, individualized planning and specialization services, responsive services, and system support. The counseling services are carried out with management principles namely planning, organizing, actuating, and evaluating.